Clinical Characterization and NPHP1 Mutations in Nephronophthisis and Associated Ciliopathies: A Single Center Experience - Soliman, Neveen A. (2012)
Nephronophthisis (NPHP) is a recessive disorder of the kidney that is the leading genetic cause of end-stage renal failure in children. Egypt is a country with a high rate of consanguineous marriages; yet, only a few studies have investigated the clinical and molecular characteristics of NPHP and related ciliopathies in the Egyptian population. We studied 20 children, from 17 independent families, fulfilling the clinical and the ultrasonographic criteria of NPHP. Analysis for a homozygous deletion of the NPHP1 gene was performed by polymerase chain reaction on the genomic DNA of all patients. Patients were best categorized as 75% juvenile NPHP, 5% infantile NPHP, and 20% Joubert syndrome-related disorders (JSRD). The mean age at diagnosis was 87.5 + 45.4 months, which was significantly late as compared with the age at onset of symptoms, 43.8 ± 29.7 months (P <0.01). Homozygous NPHP1 deletions were detected in six patients from five of 17 (29.4%) studied families. Our study demonstrates the clinical phenotype of NPHP and related disorders in Egyptian children. Also, we report that homozygous NPHP1 deletions account for 29.4% of NPHP in the studied families in this cohort, thereby confir-ming the diagnosis of type-1 NPHP. Moreover, our findings confirm that NPHP1 deletions can indeed be responsible for JSRD.